Precipitation Patterns in The Gambia from 1981 to 2020 - Ceesay, Abdoulie O.; Touray, Lamin Mai (Geographica Pannonica, 2022)
The present study used composite analysis and rainy season definition to investigate rainfall patterns in The Gambia from 1981 to 2020. Rainfall dataset as observed by 10 meteorological stations scattered across The Gambia was used. Results showed that the highest single month rainfall ever recorded in The Gambia during the study period was observed in Sapu, in the eastern sector of the country. The station recorded a total rainfall amount of 767 mm in August, 1999, while the lowest single month rainfall ever recorded was 463 mm in September 2012. It was observed in Jenoi, a station situated in the western sector of the country. Climatological results showed that the study area experienced monomodal rainfall regime during the West African Monsoon, and that the southern part of the western sector region such as Sibanor tend to receive more rainfall compared to other regions of the study area. Part of the central region receives the least annual rainfall. The eastern sector of The Gambia received much of its rain from May to October with July - September as the peak of the rain season. During May - October, Sapu received the heaviest rainfall while Fatoto received the least amount. Results also show that July - September is the period when significant amounts of rainfall are received over the eastern sector of the study area. While May and October are both transitional months, the eastern sector of the study area receives more rains in October than in May. The western sector of the study area, on the other hand, received much of its rain from June to October with July - September as the peak of the rain season. During June - October, Sibanor received the heaviest rainfall while Jenoi received the least amount. The results also show that July - September is the period when significant amounts of rainfall are received over the western sector of the study area. Although June and October are both transitional months, the western sector receives more or less the same rain amounts in June and October. Results further found that, to avert losses associated with excess or deficit in crop water requirement, in the eastern sector, crops with high water requirement should be grown before August as maximum rainfall is observed in August, whereas crops with minimum water requirement should be grown in May or October, that is when minimum rainfall is experienced. In the western sector, on the other hand, crops requiring high water amount should be grown before August or September when maximum rainfall is recorded in the sector, whereas crops with minimum water requirement should be grown in June or October. This study will help create awareness on the erratic rain seasons due to Climate Change, and to provide farmers with information on rainfall distribution in The Gambia to avert losses and impacts associated with water deficit or excess on society, agriculture, and the environment.